The safety challenge of increased cycling - CAULFIELD, BRIAN (My University, 2014)
Many countries have recently set out policy frameworks to support the growth of cycling. However, increased cycling can mean more collisions, injuries and even fatalities. This paper discusses the role of safety in cycling policy in the particular case of Ireland, which is one of the countries that has a government - endorsed policy to increase cycling. It examines available information on cycling , including police - reported accident data over the las t fifteen years and more recent hospital accident data. Comparisons are made for injuries between the two sources and data matching and capture - recapture methods used to estimate injuries. The deficiencies in data are analysed and suggestions for improveme nts made. It is argued that gaps in available data have led to accident risks being poorly understood. The paper discuss es how a convergence in cycling and safety policy can be achieved and suggests additional measures including a cycling safety target, in creased communication on cycling safety, lower urban speeds and compulsory wearing of helmets for children.
PUBLISHED
Keywords: Transport; Safety; Smart & Sustainable Planet; Road Safety